(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The aim of present study is to obtain and investigate infrared and laser Raman spectrum in their respective regions for 3,4-diethyl pyridine. During the interpretation of spectra CS point group symmetry has been assumed. The assignment of the vibrations are made in accordance with that of identical molecules as well as group frequency approach.